Experimental study on P-V diagram and valve displacement of a HC290 rotary compressor. (December 2015) - Wu, Jianhua; Wang, Gang; Li, Yuyong; Chen, Ang; Gao, Qiang; Chen, Zhenhua; Jiang, Bo
HC290 is a substitute for R22 and R410A for small heat pumps, room air conditioners, and light commercial refrigeration equipment since it has a negligible environmental impact and high efficiency. The performance, P-V diagram and valve dynamic displacement of a rotary compressor using R22 and R290 as the refrigerant, under five different operating conditions, were measured and analyzed in this paper to help understand the characteristics of internal thermodynamic process and the distribution of indicated power losses. Further, a new method for analyzing the P-V diagram of a rotary compressor was proposed. Compared with the R22 compressor, some conclusions about the discharge process starting angle, dynamic variation of pressure in the cylinder, volumetric efficiency, indicated efficiency, and loss distribution of the R290 rotary compressor under high efficiency conditions were given. The performance variation of the R290 compressor under other conditions was explained. Several measures to increase the energy efficiency of the R290 rotary compressor were proposed.